Pumped storage hydropower in Brazil and the world: application and perspectives - Canales, Fausto Alfredo; Beluco, Alexandre; Mendes, Carlos André Bulhões (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Environmental concerns and the increase of fossil fuel prices have influenced the development and expansion of renewable energy for electricity generation in Brazil and the world. Many of these technologies produce energy from unpredictable renewable sources, and this affects the operation of the electricity distribution grid, because the generation must match the demand at all times. The storage of surplus energy for using it during peak load periods can contribute to balance the load and regulate the frequency. Pumped storage hydropower plants, also known as pumped water storage or reversible hydropower is the most established technology for large scale electricity storage. This paper presents a literature review on electricity storage through pumped storage hydropower plants, and the application of this technology in the global and Brazilian scenarios. This document briefly presents and compares the available options for electricity storage, and it also describes the operating principles, environmental impacts, application, opportunities and challenges associated with reversible hydropower in the world. Finally, the development and perspectives of this technology in the Brazilian scenario are discussed.